(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Background: the segregation and exclusion of students with disabilities from general education amounts to serious violations of the right to education of these students. Objective: to determine if inclusive education guarantees fundamental rights such as; civil and political rights, accessibility, health and rehabilitation, education and sports, work and employment and social protection of people with disabilities. Results: Inclusive education in general is perceived as very efficient. The dimensions associated with inclusive education (non-discrimination, availability, physical and economic accessibility, adaptability and acceptability are perceived at a very efficient level. Conclusion: there is a perception that the fundamental rights of people with disabilities are fully guaranteed and that civil and political rights, accessibility, health and rehabilitation, education and sports, work and employment and social protection are in a very efficient level. It was evidenced that inclusive education through its dimensions guarantees the fundamental rights (civil and political rights, accessibility, health and rehabilitation, education and sports, work and employment and social protection) of people with disabilities.